2016
DOI: 10.3390/md14020020
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Potential of the Halogenated Sesquiterpene (+)-Obtusol, Isolated from the Alga Laurencia dendroidea J. Agardh (Ceramiales: Rhodomelaceae), against the Dengue Vector Mosquito Aedes aegypti (Linnaeus) (Diptera: Culicidae)

Abstract: Dengue is considered a serious public health problem in many tropical regions of the world including Brazil. At the moment, there is no viable alternative to reduce dengue infections other than controlling the insect vector, Aedes aegypti Linnaeus. In the continuing search for new sources of chemicals targeted at vector control, natural products are a promising alternative to synthetic pesticides. In our work, we investigated the toxicity of a bioactive compound extracted from the red alga Laurencia dendroidea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 55 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Seaweeds, with their great chemical diversity, are utilized as a foodstuff for human and animal food, fertilizers, cosmetics, and medicinal products [ 18 , 19 ]. Seaweed extracts have proven competence for controlling and repelling various insect pests such as cereal aphids, Schizaphis graminum [ 20 ], the cotton stainer bug, Dysdercus cingulatus [ 21 ], mosquitoes [ 22 , 23 ], the tomato moth, Tuta absoluta [ 24 ], the termite, Microtermes obesi [ 25 ], maize weevil, Sitophilus zeamais [ 26 ] and the Asian citrus psyllid, Diaphorina citri [ 27 ]. Some studies documented the insecticidal effects of seaweeds of Egyptian origin as Caulerpa prolifera , Caulerpa serrulata , Jania rubens , Nitophyllum punctatum Padina pavonica , Chara vulgaris, Parachlorella kessleri , Ulva intestinalis and Cladophora glomerata [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds, with their great chemical diversity, are utilized as a foodstuff for human and animal food, fertilizers, cosmetics, and medicinal products [ 18 , 19 ]. Seaweed extracts have proven competence for controlling and repelling various insect pests such as cereal aphids, Schizaphis graminum [ 20 ], the cotton stainer bug, Dysdercus cingulatus [ 21 ], mosquitoes [ 22 , 23 ], the tomato moth, Tuta absoluta [ 24 ], the termite, Microtermes obesi [ 25 ], maize weevil, Sitophilus zeamais [ 26 ] and the Asian citrus psyllid, Diaphorina citri [ 27 ]. Some studies documented the insecticidal effects of seaweeds of Egyptian origin as Caulerpa prolifera , Caulerpa serrulata , Jania rubens , Nitophyllum punctatum Padina pavonica , Chara vulgaris, Parachlorella kessleri , Ulva intestinalis and Cladophora glomerata [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the red algae are rich with polyphenolic and terpenes compounds compared to green and brown algae these triterpenes inhibit the protein responsible for the cholesterol transportation during the larval development resulting in larval mortality ( Blunt et al, 2011 , Bibi et al, 2020 ). In addition, halogenated sesquiterpene (−)-elatol and (+)-obtusol, brominated-oxygenated heterocyclic and halogenated, polyhalogenated compounds obtained from red algae exhibited larvicidal activity against mosquitoes ( Abou-Elnaga et al, 2011 , Salvador-Neto et al, 2016 ). Deepak et al, (2019) reported that the presence of alkyl halides, carboxylic acid, alkynes, and amides in the methanolic extract of red algae are responsible for its larvicidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The authors added that Cladophora glomerata -derived fatty acids, including myristic, palmitoleic, lauric, and capric acids, were found to have 3–14 ppm lethal concentration 50 against Aedes triseriatus . Similarly, Salvador-Neto et al ( 2016 ) reported that Laurencia dendroidea derived elatol and halogenated sesquiterpene, (+)-obtusol caused larvicidal mortality of 30% and 9%, respectively, at 10 parts per million concentrations against A. aegypti within 24 h. Additionally, obtusol extracts have shown concentration-dependent larvicidal activities. To this end, seaweed extract has promising antiviral and mosquitocidal activities, and more research is needed against more agents with different integrations and applied protocols.…”
Section: Seaweed’s Use In Pharmaceuticals and Cosmeticsmentioning
confidence: 92%